Transformational adaptation of agricultural systems to climate change. (24th April 2018) - Panda, Architesh
Abstract : This study explores the increasing use of the concept of "transformational adaptation" (TA) in the context of agriculture, analyzing its conceptualization and applications. While TA is appealing as a concept that involves the implementation of adaptation actions in different ways through small adjustments from current technological and economic approaches, it also raises questions about the complexity of transforming agricultural systems. Although current scientific evidence finds some patterns of climate change impacts on agriculture in the future that can inform the analysis of where and when transformation is required, this evidence is not enough to fully inform practical decision‐making at different scales. Part of the problem may be that there has been not enough empirical research focusing on transformational agriculture. For example, from 93 articles in the literature, 39% focus on understanding the concept of TA, 32% focus on analytical and applied aspects of TA, including studies applying global climate models to analyze TA at regional and global scales and to identify broad patterns of TA in agriculture, and only 16% have tried to understand TA from an empirical perspective. While the number of empirical studies of TA is still increasing, there are other issues of TA that have received limited attention, including uncertainty of climate change impacts, policy implications, the transition process, the role of technological innovations, and barriers to TA. This article is categorized under: Vulnerability and Adaptation to Climate Change > Values‐Based Approach to Vulnerability and Adaptation Abstract : Yearly distribution of selected publications on transformational adaptation.